2000
DOI: 10.1089/15230860050192323
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Metabolic Control of the Mitochondrial Transmembrane Potential and Reactive Oxygen Intermediate Production in HIV Disease

Abstract: Redox mechanims play important roles in replication of human immunodeficiency virus type 1 (HIV-1) and cellular susceptibility to apoptosis signals. Viral replication and accelerated turnover of CD4+ T cells occur throughout a prolonged asymptomatic phase in patients infected by HIV-1. Disease development is associated with steady loss of CD4+ T cells by apoptosis, increased rate of opportunistic infections and lymphoproliferative diseases, disruption of energy metabolism, and generalized wasting. Such patholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
63
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(64 citation statements)
references
References 211 publications
1
63
0
Order By: Relevance
“…22 Previous studies showed that ROS production was partially controlled by genetic factors. 23 We also observed a difference in ROS production between inbred mouse strains with the FVB/N producing higher ROS than the DBA/1 strain (data not shown). In this study, we identified the first QTL controlling ROS production in mice.…”
Section: Resultsmentioning
confidence: 65%
“…22 Previous studies showed that ROS production was partially controlled by genetic factors. 23 We also observed a difference in ROS production between inbred mouse strains with the FVB/N producing higher ROS than the DBA/1 strain (data not shown). In this study, we identified the first QTL controlling ROS production in mice.…”
Section: Resultsmentioning
confidence: 65%
“…antioxidants present in human serum become insufficient to circumvent HIV-1 replication secondary to cellular ROS production (superoxide anion, hydroxyl radical, hydrogen peroxide etc.) by a pro-oxidant effect of inflammatory cytokines and/or a polymorphonuclear leukocyte activation [13].…”
Section: Introductionmentioning
confidence: 99%
“…Disruption of the mitochondrial membrane potential has been proposed as the point of no return in apoptotic signaling (19 -21). Metabolic fluxes between glycolysis and the PPP are particularly relevant for maintaining the mitochondrial transmembrane potential (Dc m ) and balancing cellular requirements for energy and ROI production (18,22).…”
Section: Introductionmentioning
confidence: 99%